2020
DOI: 10.1093/nar/gkaa1090
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitinase USP36 Regulates DNA replication stress and confers therapeutic resistance through PrimPol stabilization

Abstract: PrimPol has been recently identified as a DNA damage tolerant polymerase that plays an important role in replication stress response. However, the regulatory mechanisms of PrimPol are not well defined. In this study, we identify that the deubiquitinase USP36 interferes with degradation of PrimPol to regulate the replication stress response. Mechanistically, USP36 is deubiquitinated following DNA replication stress, which in turn facilitates its upregulation and interaction with PrimPol. USP36 deubiquitinates K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…The increase in mRNA was found to be regulated by ATR. Another recent study reported that the USP36 protease also possibly plays a role in regulating PrimPol protein levels ( 152 ), and the ATPase WRNIP1 has been suggested to target PrimPol protein for degradation ( 153 ). This suggests that multiple mechanisms exist that regulate PrimPol deployment in human cells.…”
Section: Introduction: the Eukaryotic Dna Replication Machinerymentioning
confidence: 99%
“…The increase in mRNA was found to be regulated by ATR. Another recent study reported that the USP36 protease also possibly plays a role in regulating PrimPol protein levels ( 152 ), and the ATPase WRNIP1 has been suggested to target PrimPol protein for degradation ( 153 ). This suggests that multiple mechanisms exist that regulate PrimPol deployment in human cells.…”
Section: Introduction: the Eukaryotic Dna Replication Machinerymentioning
confidence: 99%
“…Staining intensity was scored using a four-point scale as follows: 3, strong (tan); 2, medium (brown-yellow); 1, weak (light yellow); and 0, none. The proportion of positive cells was scored as 0, 0%; 1, ≤10%; 2, 11–50%; 3, 51–75%; and 4, >75% ( 20 ). The staining index (SI) was determined as the sum of the staining intensity score and the number of positive cells.…”
Section: Methodsmentioning
confidence: 99%
“…Ubiquitinase and deubiquitinase, therefore, make them effective therapeutic targets against drug resistance by epigenetic regulation of a variety of cancer-related pathways and their ability to regulate atypical drug targets such as transcription factors and skeleton proteins (53). It has been reported that deubiquitinase is abnormally activated in a variety of cancers, resulting in increased protein expression related to drug efflux and changes in drug target molecules (54), activating a variety of oncogenic pathways and forming drug resistance (55)(56)(57), so deubiquitinase has the potential to be developed as drug targets. It is therefore essential to study the ubiquitylome of cancers to provide new ideas for new drug target development.…”
Section: Discussionmentioning
confidence: 99%